Transcranial direct current stimulation of the primary motor cortex improves word-retrieval in older adults - Meinzer, Marcus; Lindenberg, Robert; Sieg, Mira M.; Nachtigall, Laura; Ulm, Lena; Flöel, Agnes (Frontiers in Aging Neuroscience, 2014)
Language facilitation by transcranial direct current stimulation (tDCS) in healthy individuals has generated hope that tDCS may also allow improving language impairment after stroke (aphasia). However, current stimulation protocols have yielded variable results and may require identification of residual language cortex using functional magnetic resonance imaging (fMRI), which complicates incorporation into clinical practice. Based on previous behavioral studies that demonstrated improved language processing by motor system pre-activation, the present study assessed whether tDCS administered to the primary motor cortex (M1) can enhance language functions. This proof-of-concept study employed a sham-tDCS controlled, cross-over, within-subject design and assessed the impact of unilateral excitatory (anodal) and bihemispheric (dual) tDCS in eighteen healthy older adults during semantic word-retrieval and motor speech tasks. Simultaneous fMRI scrutinized the neural mechanisms underlying tDCS effects. Both active tDCS conditions significantly improved word-retrieval compared to sham-tDCS. The direct comparison of activity elicited by word-retrieval vs. motor-speech trials revealed bilateral frontal activity increases during both anodal- and dual-tDCS compared to sham-tDCS. This effect was driven by more pronounced deactivation of frontal regions during the motor-speech task, while activity during word-retrieval trials was unaffected by the stimulation. No effects were found in M1 and secondary motor regions. Our results show that tDCS administered to M1 can improve word-retrieval in healthy individuals, thereby providing a rationale to explore whether M1-tDCS may offer a novel approach to improve language functions in aphasia. fMRI revealed neural facilitation specifically during motor speech trials, which may have reduced switching costs between the overlapping neural systems for lexical retrieval and speech processing, thereby resulting in improved performance.